2011
DOI: 10.1111/j.1399-3046.2011.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Living‐donor liver transplantation for propionic acidemia

Abstract: Propionic acidemia is a rare autosomal recessive disorder affecting the catabolism of branched-chain amino acids because of a genetic defect in PCC. Despite the improvements in medical treatment with protein restriction, sufficient caloric intake, supplementation of l-carnitine, and metronidazole, patients with the severe form of propionic acidemia have life-threatening metabolic acidosis, hyperammonemia, and cardiomyopathy, which results in serious neurologic sequelae and sometimes death. This study retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 14 publications
2
47
0
Order By: Relevance
“…Despite these, when LT is successful, we and others (11,(14)(15)(16) have shown that the quality of life of the surviving patients is transformed. Acute metabolic decompensations are abolished, with a follow-up up to 21 years.…”
Section: Discussionmentioning
confidence: 95%
“…Despite these, when LT is successful, we and others (11,(14)(15)(16) have shown that the quality of life of the surviving patients is transformed. Acute metabolic decompensations are abolished, with a follow-up up to 21 years.…”
Section: Discussionmentioning
confidence: 95%
“…However, experience with LT in PA is still limited. Recent case studies have reported clinical improvement, including significant decrease of episodes of metabolic decompensation, better feeding, and improved neurological development after LT [187,200]. Moreover, LT has been shown to effectively reverse cardiomyopathy [44,201].…”
Section: Methodology and Objectivesmentioning
confidence: 99%
“…Cardiomyopathy [21,23,26,31,39,43,44,71,148,260] and prolonged QTc interval [21,31,38,40,41,56] are emerging as potentially lethal complications in MMA and, more prominently, PA. Additionally there are several reports of heart failure in patients with MMA and PA who did not have cardiomyopathy [187,261,262]. Median age of presentation of cardiomyopathy was 7 years [44].…”
Section: Methodology and Objectivesmentioning
confidence: 99%
“…The median age at transplant was 3 years with a median follow‐up of 2.5 years (range, 0.01‐21 years). Preexisting cardiomyopathy was reversed in all 10 reported patients . The most common reported complication was HAT occurring in 25% of the grafts.…”
Section: Discussionmentioning
confidence: 87%
“…Since 1992, 49 patients (56 grafts) with PA and LT have been reported (Table ) . The median age at transplant was 3 years with a median follow‐up of 2.5 years (range, 0.01‐21 years).…”
Section: Discussionmentioning
confidence: 99%